(untitled) (International Conference on Computers in Education, 2023)
Soft skills play a major role in the success of software development projects. However, learning soft skills is difficult. Video-based learning (VBL) provides self-paced and flexible learning but is often a passive method. Therefore, Active Video Watching (AVW) has been proposed to increase engagement and learning. We investigate gamification as an intervention to enhance the soft skill training of software professionals using AVW. The proposed research method includes both quantitative and qualitative approaches.